Between Reform and Reality: Social Marginalization and Public Health Challenges for Migrant Farmers in Rural China - Wang, Hengyu (Social Welfare: Interdisciplinary Approach, 2025)
Migrant farmers in China face severe social marginalization and public health challenges. Through participant observation and 52 semi-structured interviews, this study explores the structural factors and the systemic contradictions between their social marginalization and public health challenges. The findings reveal that inadequate reforms of the household registration system (the hukou system) and the political tasks in agriculture jointly shape the social marginalization of migrant farmers. The insufficiencies of the public health system in addressing migrants’ everyday healthcare needs highlight the relationship between identity and an exclusionary healthcare supply, harming their health and exacerbating potential risks. While reforms in social health insurance have improved the overall coverage, they have failed to fully address issues of underinsurance, marginalized status, and healthcare accessibility, thus leaving the structural inequality of migrant farmers’ healthcare unresolved. Moreover, their marginalized identity significantly impacts their mental health, as they endure persistent discrimination and disciplinary power, which poses long-term risks to their well-being. This study provides valuable insights into the mechanisms of social marginalization and public health challenges faced by migrant farmers in China.
Keywords: Social marginalization; Public health; Migrant farmers; China